2018
DOI: 10.1016/j.oooo.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chemotherapeutic treatment on the oral microbiota of patients with cancer: a systematic review

Abstract: During chemotherapy, patients with cancer present a more complex oral microbiota under favorable conditions for their development during immunosuppression, and these may be responsible for different serious local or systemic pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…However, this association was only reported in patients treated with surgery and chemoradiation as compared to patients treated with just surgical removal of the tumor and to healthy controls. This suggests that chemoradiation might cause the increased relative abundance of these bacteria, which is in line with the known presence of a more complex oral microbiota in cancer patients treated with chemotherapy [70]. The relative abundance of the genus Capnocytophaga was found decreased in saliva samples of healthy controls in an OSCC study [63].…”
Section: Streptococcussupporting
confidence: 54%
See 1 more Smart Citation
“…However, this association was only reported in patients treated with surgery and chemoradiation as compared to patients treated with just surgical removal of the tumor and to healthy controls. This suggests that chemoradiation might cause the increased relative abundance of these bacteria, which is in line with the known presence of a more complex oral microbiota in cancer patients treated with chemotherapy [70]. The relative abundance of the genus Capnocytophaga was found decreased in saliva samples of healthy controls in an OSCC study [63].…”
Section: Streptococcussupporting
confidence: 54%
“…In some cases, such as the study by Olson et al [76], the selection criteria were so strict that from 281 approached patients, 80% were considered ineligible for various reasons, most importantly because they had been previously treated with chemotherapy. The previous history of treatment with neo-adjuvant chemotherapy or chemoradiation influences substantially the microbiome profile [70]. Therefore, all the criteria followed for the selection of patients and control subjects should be well-documented and taken into account when performing the statistical analyses of results.…”
Section: Phc Gac Crcmentioning
confidence: 99%
“…A chemotherapy-induced increase in oral commensal bacterial burdens, particularly aciduric bacteria such as Lactobacilli and Streptococci has also been reported in a chemotherapy treated breast cancer cohort [42]. Moreover, a recent systematic review focusing on evaluation of the impact of chemotherapeutic treatment on the oral microbiota in patients with cancer showed that during chemotherapy, there is an increase in bacteria of the Enterobacteriaceae family and in Streptococcus species, potentially contributing to local oral manifestations, such as oral mucositis, or even systemic infections such as septicemia [43]. Finally, HIV infection was recently associated with lower richness and diversity estimates in the oral bacterial microbiome, with several taxa having increased abundance in this host background.…”
Section: Immunocompomised Hosts Have Altered Oral Bacterial Microbiommentioning
confidence: 87%
“…Klebsiella spp. is the main bacterium in the oral flora during the immunosuppression of cancer patients, which may lead to severe local or systemic disease in these patients (114). We believe that the changes in the intestinal flora of patients with sporadic NPC can lead to the disruption of the immune function by promoting inflammation that triggers cancer and may also affect the liver function.…”
Section: Discussionmentioning
confidence: 99%